Possible beneficial effect of statin in women with poly cystic ovarian syndrome (PCOs) - Sarah Al Ramadhan (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Statins, as lipid-lowering agents are likely not only to improve the dyslipidaemia associated with polycystic ovary syndrome but may also exert other beneficial metabolic and endocrine effects. Aim of the study: Reviewing, assessing the possible beneficial effect of statins therapy in women with poly cystic ovarian syndrome conceive. Search method: Electronic searching of databases including published Cochrane library, Menstrual Disorders and Subfertility Group Trials Register, the Cochrane Central Register of Controlled Trials (CENTRAL) , MEDLINE ,EMBASE , PubMed in English language up to February 2016 using the following keywords: Polycystic ovary syndrome, ovary polycystic disease, PCOS Statin, Atorvastatin, Simvastatin, Rosuvastatin, Lovastatin, Mevastatin, Pravastatin. Inclusion Criteria: randomised studies in which any statin was compared with placebo or other agent(s), or any statin in combination with another drug was compared to another class of drug alone in women with PCOS are included , non randomized controlled trials were excluded . Data collection: selecting trials that have the inclusion criteria from the search results , printed and collecting data from each study for results presented using , excluded studies that did not meet the inclusion criteria Main results: Four trials fulfilled the criteria for inclusion. They comprised a total of 244 women with PCOS receiving 12 weeks or 6 weeks of treatment. Two trials (184 women randomised) studied the effects of simvastatin and two trials (60 women randomised) studied the effects of atorvastatin. There was no good evidence that statins improved menstrual regularity, spontaneous ovulation rate, hirsutism or acne, either alone or in combination with the combined oral contraceptive pill (OCP). Nor were there any significant effects on body mass index (BMI). Statins were effective in lowering testosterone levels (nmol/L) (mean difference (MD) -0.90, 95% CI -1.18 to -0.62, P < 0.00001, 3 RCTs, 105 women) when used alone or with the OCP. Statins also improved total cholesterol, low-density lipoprotein (LDL) and triglycerides but had no significant effect on high-density lipoprotein (HDL) levels, high sensitivity (HS) Creactive protein (HS-CRP), fasting insulin or homeostatic model assessment (HOMA) insulin resistance. No serious adverse events were reported in any of the included studies. Conclusions: Statins are effective in improving the lipid profile of women with PCOS, Statins, either alone or with the oral contraceptive pill (OCP), also improve the biochemical parameter of hyperandrogenaemia (reducing the level of total testosterone) but There is no good evidence that statins improve menstrual regularity, ovulation rate, hirsutism or acne in women with polycystic ovary syndrome (PCOS), and there are no data on the long term safety of statins in women with PCOS, no data are available about the long-term cardiovascular risk profile in women with PCOS